Guiding the Public Sector: Assessing the Use of Recommended Practices in the Budgeting Process. Issue 7 (7th June 2017) - Helpap, David J.
ABSTRACT: Public administration is a field defined by principles, best practices, and recommended guidelines. According to advocates, these guidelines have the potential to improve the effectiveness and efficiency of public organizations. However, this potential is predicated on the degree to which they are actually followed in practice. Using an original survey of local budgeting officials across the United States, this study examines the correlation between current budgeting practices and established, recommended practices. While a significant number of current practices closely match those that have been recommended, notable variations were present. The trends and their implications conclude the assessment.